Practices, Pedagogies, and Desires: Untethering Research - Andrew, David; Barry, Hedwig (Arts Research Africa, The Wits School of Arts, University of the Witwatersrand, 2020)
What does it mean to engage in artistic research over a period of a one-year Master of Arts in Fine Arts (MAFA) project? In this discussion, a student (Barry) and supervisor (Andrew) reflected on this digressionary trajectory from the vantage point of the Global South.
What does it mean to engage in artistic research over a period of a one-year Master of Arts in Fine Arts (MAFA) project? In this discussion, a student (Barry) and supervisor (Andrew) reflected on this digressionary trajectory from the vantage point of the Global South.
Keywords: artistic research, arts research, decolonisation, arts pedagogy